MYBL2 promotes cell proliferation and inhibits cell apoptosis via PI3K/AKT and BCL2/BAX/Cleaved-caspase-3 signaling pathway in gastric cancer cells - Chen, Jingya; Ji, Zhenglei; Wu, Di; Wei, Siyang; Zhu, Wanjing; Peng, Guisen; Hu, Mingjie; Zhao, Yunli; Wu, Huazhang (Scientific reports, 2025)
The transcription factor MYB proto-oncogene like 2 (MYBL2) has been reported to be involved in the occurrence and development of various tumors, however, its role in gastric cancer (GC) remains to be elucidated. In this study, the Kaplan-Meier plotter was used to evaluate the prognostic value of different MYBL2 expression levels in GC patients. The UALCAN database were applied to analyze the relationships between MYBL2 and clinicopathological characteristics of GC. GC cell proliferation, cell cycle and apoptosis were determined by CCK-8 and flow cytometry assays, and proteins were examined by Western blot analysis. Next, signaling pathway enrichment analysis of MYBL2-related genes and protein expression were analyzed by Gene Set Enrichment Analysis (GSEA) and Western blot assays. The results found that MYBL2 expression was significantly upregulated in GC compared with adjacent non-malignant tissues and associated with poor patient survival, tumor, stages and lymph node metastasis. Forced expression of MYBL2 could promote cell proliferation, resulting in an accelerated S phase progression and inhibiting cell apoptosis in GC cells. Conversely, MYBL2 silencing inhibited cell proliferation, induced G2/M phase arrest and promoted cell apoptosis in GC cells. Mechanistically, Western blot analysis showed that MYBL2 silencing decreased the expression of BCL2 and upregulated the expression of Cleaved-caspase-3 and BAX in HGC-27 cells. Conversely, MYBL2 overexpression in AGS cells resulted in the opposite effects. Furthermore, enforced expression of MYBL2 activated the PI3K/AKT signaling pathway, especially AKT phosphorylation. Additionally, the AKT inhibitor MK2206 significantly reversed the proliferation capacity of GC cells induced by MYBL2 overexpression. Therefore, these results suggest that upregulated expression of MYBL2 contributes to GC cell growth and inhibits cell apoptosis by regulating the PI3K/AKT and BCL2/BAX/Cleaved-caspase-3 signaling pathways in GC cells indicating that MYBL2 may be a new therapeutic target and prognostic marker for GC.